Short-term psychological consequences of the COVID-19 pandemic: Results of the first wave of an ecological daily study in the Italian population. (November 2021) - Preti, Emanuele; Pierro, Rossella Di; Perego, Gaia; Bottini, Marta; Casini, Erica; Ierardi, Elena; Madeddu, Fabio; Mazzetti, Martina; Riva Crugnola, Cristina; Taranto, Paola; Mattei, Valentina Di
Highlights: We monitored the mental health of Italian adults during the COVID-19 lockdown. Distress was associated with demographic conditions and perception of the situation. Risk factors: worse representation of COVID-19 and consulting news more frequently. Risk factors: female gender, younger age, high-risk regions, symptoms of COVID-19. Protective factors: social support and cognitive reappraisal. Abstract: COVID-19 pandemic involved several psychosocial consequences. We aimed at monitoring the mental health of Italian adults during the lockdown imposed by the government. We present here results from the baseline assessment of the "EmotionalThermometer [TermometroEmotivo] project on a sample of 1548 Italian adults. We assessed the socio-demographic conditions of participants, individuals' perception of the COVID-19-situation, psychological distress, emotion regulation strategies, and perceived social support. Having a worse representation of COVID-19 and consulting news more frequently, with higher anxiety and less credibility of different sources of information, were positively associated with psychological distress and post-traumatic responses. Being female, younger age, living in high-risk regions, having symptoms of COVID-19, and having relatives/friends with such symptoms represented risk factors for a worse perception of COVID-19 and distress. Social support and cognitive reappraisal represented protective factors for mental health.